Desenvolvimento de nano e micropartículas de quitosana encapsulando 4-metilesculetina e avaliação no tratamento da doença inflamatória intestinal - Masago, Fabiana [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Ulcerative colitis and Crohn's disease, the main forms of Inflammatory Bowel Disease (IBD), are chronic diseases which cause abdominal pain, diarrhea and bleeding. Nowadays, the available treatments, such as aminosalicylates, glucocorticoids, immunosuppressants and biological therapy with monoclonal antibodies do not promote a definitive cure; furthermore, they are associated with several side effects. Recent studies showed protective effects of coumarin derivative 4-methylesculetin (4-ME) against colonic inflammation induced by 2,4,6-trinitrobenzenesulphonic acid (TNBS), which was associated to the anti-inflammatory and antioxidant properties of 4-ME. Since encapsulation of drugs and active products into nano and microparticles are able to increase the retention time in the colon and improve pharmacology activity; the present study aims to develop chitosan nano and microparticles containing 4-ME, and to evaluate if these pharmaceutical formulations improve intestinal anti-inflammatory activity 4-ME when compared to its free form. For this, nano and microparticles of chitosan with 4-ME encapsulated were standardized, which were administered, by oral route, at the dose of 5 mg/Kg, and its effects compared with same dose of free form of 4-ME, using the TNBS model of colonic inflammation in rats. In this context, macroscopic (score, lesion extension, weight/length ratio and adherence) and biochemical (myeloperoxidase and alkaline phosphatase activities and total glutathione content) parameters were analyzed. Treatments with nano and microparticles were not able to minimize TNBS-induced inflammation; however, free form 4-ME demonstrated anti-inflammatory activity evidenced by the significant inhibition of alkaline phosphatase activity and counteraction of glutathione depletion. In conclusion, 4-ME associated with nano and microparticles of chitosan did not represent an appropriated pharmacologic strategy for the controlled delivery of 4-ME ...

A retocolite ulcerativa e a Doença de Crohn, as principais formas de Doença Inflamatória Intestinal (DII), são doenças crônicas do intestino que causam dores abdominais, diarreia intensa e hemorragias. Até o momento, os tratamentos farmacológicos disponíveis, que incluem aminosalicilatos, glicocorticóides, imunossupressores e a terapia biológica com anticorpos monoclonais, não promovem a cura definitiva da doença e estão associados ao desenvolvimento de diversos efeitos colaterais. Recentes estudos mostraram que o derivado cumarínico 4-metilesculetina (4-ME) possui efeitos protetores no processo inflamatório colônico induzido por ácido 2,4,6-trinitrobenzenosulfônico (TNBS), os quais foram associados às suas atividades anti-inflamatória e antioxidante. Considerando-se que a encapsulação de fármacos e produtos ativos em nano e micropartículas poderiam aumentar seu tempo de retenção no cólon com consequente aumento da resposta farmacológica, os objetivos do presente trabalho foram elaborar nano e micropartículas de quitosana contendo 4-ME e avaliar se estas formulações melhoram a resposta anti-inflamatória intestinal da 4-ME em comparação à sua administração na forma livre. Para tal, foi realizada a padronização de micro e nanopartículas de quitosana contendo 4-ME, as quais foram administradas, por via oral em ratos, na dose de 5 mg/Kg e seus efeitos comparados com a administração da mesma dose de 4-ME na forma livre, usando o modelo de inflamação colônica induzida por TNBS em ratos. Neste contexto, foram avaliados parâmetros macroscópicos (escore da lesão, extensão da lesão, relação peso/comprimento do cólon e aderência) e bioquímicos (atividade da mieloperoxidase e da fosfatase alcalina e níveis colônicos de glutationa total). Os tratamentos com micro e nanopartículas não foram capazes de diminuir a inflamação induzidas pelo TNBS; contudo a administração de 4-ME em sua forma livre...
Keywords: Cumarínicos; Nanopartículas; Microesfera; Doenças inflamatórias intestinais; Quitosana; Inflammatory bowel deseases; Coumarins